Morphological characterization of the ovary and vitellogenesis dynamics in the tick Amblyomma cajennense (Acari : Ixodidae) - Denardi, S. E.; Bechara, G. H.; de Oliveira, P. R.; Nunes, E. T.; Saito, K. C.; Mathias, Maria Izabel Camargo [UNESP] (Elsevier B.V., 2004)
In this work we describe the internal morphology of the female reproductive system of the cayenne tick Amblyomma cajennense. This system is represented by a panoistic ovary, which lacks nurse cells in the germarium. This ovary consists of a single tube, in which a large number of oocytes develop asynchronously, thus accompanying the processes of yolk deposition in the oocytes. The oocytes were classified into stages that varied from I to V, according to: cytoplasm appearance, presence of the germ vesicle, presence of yolk granules, and presence of chorion. The study of vitellogenesis dynamics suggest that the yolk elements are deposited in the oocyte following a preferencial sequence, in which the lipids are the first to appear, followed by proteins an finally by the carbohydrates. In this way the yolk of A. cajennense ticks have these three elements that may be free in the cytoplasm or chemically bounded forming glycoprotein or lipoprotein complexes. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Amblyomma cajennense; oocytes; tick; histology; histochemistry; ultrastructure-vitellogenesis